Optical camera communication for driver’s assistance systems - Soares, Miguel Ângelo Roque (2020)
Communications, whatever its type, is a pillar of our modern society. More specifically, communications by visible light, that show numerous advantages, from electromagnetic spectral efficiency and regulation freedom to energy saving (since it combine illumination and communication). As such, the automotive world is interested in this technology, in particularly, its application into the Intelligent Transport System (ITS). The objective of this work relies on the study and development of a demonstrator able to support VLC communication means in V2V (Vehicle to Vehicle) scenario, making use of the LED luminaries already implemented in nowadays cars. Since the outdoor implementation is one of the requirements, reception based in OCC (Optical Camera Communication) is a viable solution in this conditions. Also the signal processing/decoding is performed by a CNN (Convolutional Neural Network), this type of algorithm shows a huge decoding flexibility and resilience, which benefits the transmission system performance. All the project was done in collaboration with the integrated circuits systems group of Instituto de Telecomunicações de Aveiro and Exatronic Lda company, based in Aveiro and specialized in innovation and investigation (I+I), engineering and manufacturing of electronics.